1994
DOI: 10.3109/00365549409008653
|View full text |Cite
|
Sign up to set email alerts
|

Legionella Urinary Antigen in Early Disease

Abstract: The results of Legionella urinary antigen testing were correlated to the interval between onset of disease and sampling of urine in 134 patients in connection with a large outbreak of Legionnaires' disease at a Swedish hospital. In 17 patients with the disease, 5/7 sampled during the first 5 days of illness proved negative in the urinary antigen test. The risk of obtaining negative results during the first days of the disease is emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Sensitivity of the immunochromatographic assay is 55.5% and 97.2% on unconcentrated and concentrated urine specimens, respectively [105]. The assay may be negative in some patients during the first 5 days of the disease and remain positive for between 6-14 days [106].…”
Section: What Can Antigen Tests Offer In the Diagnosis Of Cap?mentioning
confidence: 99%
“…Sensitivity of the immunochromatographic assay is 55.5% and 97.2% on unconcentrated and concentrated urine specimens, respectively [105]. The assay may be negative in some patients during the first 5 days of the disease and remain positive for between 6-14 days [106].…”
Section: What Can Antigen Tests Offer In the Diagnosis Of Cap?mentioning
confidence: 99%
“…In studies comparing urinary antigen testing, DFA, and culture, the authors concluded that urinary antigen detection was the most useful test (230). Several studies assessing the overall sensitivity (all Legionella infections, not just L. pneumophila serogroup 1) of the Binax Equate Legionella Urinary Antigen kit determined this to range from 53 to 56% (29,226). A major drawback of urinary antigen testing with the RIA is the difficulty involved in the handling and disposal of radioisotopes required to perform RIA.…”
Section: Urine Antigen Detectionmentioning
confidence: 99%
“…Regardless of the species or serogroup, clinicians should be particularly aware of in vitro diagnostic limitations when ruling out LD. A negative UAT does not necessarily exclude LD from consideration (304), because severe disease is more likely to yield a positive test (as opposed to mild LD), and results can vary greatly with time since exposure (141,259,(305)(306)(307). These complications were confirmed in several research studies, where presumably low antigen excretion presented "delayed positive" ICT results (using the BinaxNOW Legionella ICT) observed at later time points (e.g., after 1 to 4 h of incubation) for samples initially giving borderline EIA absorbance measurements (267,268,276,308).…”
Section: Urinary Antigen Testmentioning
confidence: 99%
“…However, with some commercial products, this procedure may occasionally yield false-positive results, and manufacturers typically do not endorse this method of use (with some exceptions, e.g., Oxoid Xpect); in any case, results should be interpreted with caution if this method is performed (278,309). In general, if initial UAT results are negative but the index of suspicion for LD remains high, clinicians are encouraged to perform testing multiple times over a longer period and/or to employ alternative testing modalities, such as PCR (283,305), and additionally, concentrating urine can increase sensitivity without decreasing specificity (266,279,283,306); however, boiling to reduce nonspecific interactions may be advised. These additional steps would likely abrogate the time advantages of the rapid ICT.…”
Section: Urinary Antigen Testmentioning
confidence: 99%